Biosurfactants: A Covid-19 Perspective - Smith, Matthew L.; Gandolfi, Stefano; Coshall, Philippa M.; Rahman, Pattanathu K. S. M. (Frontiers in Microbiology, 2020)
The recent outbreak Covid-19 has demonstrated the complete inability of nations across the world to cope with the pressures of a global pandemic, especially one in which the only current feasible treatments are those which deal with the symptoms alone and not the viral cause. In this case, the use of biosurfactants in dealing with this pandemic justifies extensive study with their potential applications being in the prevention of viral spread; dealing with the symptoms that develop after the incubation period; directly targeting viral infected cells and preventing the spread of the virus throughout the host, all in addition to also acting as potential drug delivery systems and cleaning agents. This extensive avenue of biosurfactants owes to the simplicity in their amphiphilic structure which permits them to interact directly with the lipid membrane of the coronavirus, in a way which wouldn’t be of significant threat to the host. Although it could possibly interact and affect the virus, it could also affect human internal organs/cells by interacting with lipid membrane, if (biosurfactant is) ingested, and it still needs further studies in human models. The structure of the coronavirus, in this case SARS-COV-2, is detrimentally dependent on the integrity of its lipid membrane which encloses its vital proteins and RNA. Biosurfactants possess the innate ability to threaten this membrane, a result of their own hydrophobic domains across their amphiphilic structure. With biosurfactants additionally being both natural and sustainable with low cytotoxicity and increasing its significance in dealing with the current pandemic.